Hubungan Kafein dan Durasi Tidur Terhadap VO2Max pada Siswa Sekolah Sepak Bola Surabaya - Arya Indra Rabbani; Agung Budi Dharmawan (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
This study aims to analyze the relationship between caffeine consumption and sleep duration on VO₂Max levels among soccer school (SSB) students in Surabaya. VO₂Max is a key indicator of cardiorespiratory fitness and athletic performance. This research employed a quantitative cross-sectional design with an analytical observational approach. A total of 162 SSB students were included as research participants from several soccer schools in Surabaya. Data were collected using the Food Frequency Questionnaire (FFQ) to assess caffeine intake and the Pittsburgh Sleep Quality Index (PSQI) to evaluate sleep duration, and were analyzed using the Chi-Square test. The results revealed a significant relationship between caffeine consumption and sleep duration with VO₂Max (p<0.001). Students with higher caffeine consumption (≥3.5) and adequate sleep duration (≥7 hours) tended to have better VO₂Max values compared to those with lower caffeine intake and insufficient sleep. These findings indicate that appropriate caffeine consumption and adequate sleep duration play an important role in improving cardiorespiratory fitness. Therefore, proper education on healthy lifestyle habits is essential to optimize the performance of young athletes.